Nahj al-Balāghah: The Wisdom and Eloquence of ʿAlī : A Parallel English-Arabic Text - Qutbuddin, Tahera (Islamic Translation Series, 2024)
Nahj al-BalÄghah , the celebrated compendium of orations, letters, and sayings of Ê¿AlÄ« ibn AbÄ« á¹¬Älib (d. 40/661) compiled by al-SharÄ«f al-Raá¸ōÄ« (d. 406/1015), is a masterpiece of Arabic literature and Islamic wisdom studied and memorized avidly and continually for over a thousand years. Showcasing Ê¿AlÄ«'s life and travails in his own words, it also transcribes his profound reflections on piety and virtue, and on just and compassionate governance. Tahera Qutbuddin's meticulously researched critical edition based on the earliest 5th/11th-century manuscripts, with a lucid, annotated facing-page translation, brings to the modern reader the power and beauty of this influential text, and confirms the aptness of Raá¸ōÄ«'s title, "The Way of Eloquence."